Hypoglycaemia‐free artificial pancreas project. Issue 1 (1st February 2020) - Magdelaine, Nicolas; Rivadeneira, Pablo S.; Chaillous, Lucy; Fournier‐Guilloux, Anne‐Laure; Krempf, Michel; MohammadRidha, Taghreed; Ait‐Ahmed, Mourad; Moog, Claude H.
Abstract : Driving blood glycaemia from hyperglycaemia to euglycaemia as fast as possible while avoiding hypoglycaemia is a major problem for decades for type‐1 diabetes and is solved in this study. A control algorithm is designed that guaranties hypoglycaemia avoidance for the first time both from the theory of positive systems point of view and from the most pragmatic clinical practice. The solution consists of a state feedback control law that computes the required hyperglycaemia correction bolus in real‐time to safely steer glycaemia to the target. A rigorous proof is given that shows that the control‐law respects the positivity of the control and of the glucose concentration error: as a result, no hypoglycaemic episode occurs. The so‐called hypo‐free strategy control is tested with all the UVA/Padova T1DM simulator patients (i.e. ten adults, ten adolescents, and ten children) during a fasting‐night scenario and in a hybrid closed‐loop scenario including three meals. The theoretical results are assessed by the simulations on a large cohort of virtual patients and encourage clinical trials.